From Textualism to Contextual Justice: Applying Aswaja Nahdlatul Ulama Values to Maqāṣid-Based Legal Moderation in Indonesian Islamic Courts - Ahmad Muhamad Mustain Nasoha; Ari Hikmawati; Ashfiya Nur Atqiya; Zamzam and Ar Rahbin; Muhammad Nur Ukasyah; Viror Ghufron Assaifi; Imam Abdullah (Journal of Nahdlatul Ulama Studies, 2026)
This article offers a novel reconstruction of legal reasoning in Indonesian Islamic courts by proposing a Constitutional Maqāṣid framework that bridges the long-standing tension between textualism and contextual justice. While existing adjudicative practices often oscillate between rigid adherence to statutory texts and fragmented contextual considerations, this study argues that both approaches remain insufficient to address the complexity of contemporary socio-legal realities. The novelty of this research lies in the integration of maqāṣid al-sharīʿah with constitutional values particularly justice, human dignity, and legal certainty into a unified interpretive model termed Constitutional Maqāṣid Justice (CMJ). Employing a normative juridical method combined with conceptual and statutory approaches, this study critically examines judicial reasoning patterns within Indonesian Islamic courts and identifies a persistent gap between formal legality and substantive justice. The proposed CMJ framework repositions judges not merely as appliers of legal texts, but as ethical interpreters who harmonize Qur’anic objectives, statutory provisions, and constitutional mandates. Through this synthesis, maqāṣid principles such as the protection of religion, life, intellect, lineage, and property are elevated from moral guidance to operative constitutional reasoning tools. The findings demonstrate that the Constitutional Maqāṣid approach enables a more adaptive, proportional, and humanistic form of legal moderation. It ensures that judicial decisions remain legally grounded while being socially responsive and normatively transformative. Furthermore, this model contributes a new theoretical paradigm within Islamic legal studies by embedding maqāṣid within a constitutional framework, thus advancing a form of Islamic sociological jurisprudence that is both context-sensitive and institutionally legitimate. Ultimately, this research not only enriches the discourse on legal moderation in Muslim societies but also offers a practical blueprint for reforming judicial reasoning in pluralistic constitutional systems like Indonesia.